Materials for printed boards and other interconnecting structures. Reinforced base materials clad and unclad. High performance, non-halogenated epoxide woven E-glass laminate sheets of defined flammability (vertical burning test), copper-clad for lead-free assembly Part 2-40, (30th April 2013) - British Standards Institution,
No abstract available